2018
DOI: 10.1007/s00011-018-1192-1
|View full text |Cite
|
Sign up to set email alerts
|

MiR-200b attenuates IL-6 production through IKKβ and ZEB1 in human gingival fibroblasts

Abstract: ObjectiveMicroRNAs (miRNAs) play important roles in biological processes such as cell differentiation, development, infection, immune response, inflammation and tumorigenesis. We previously reported that the expression of miR-200b was significantly increased in inflamed gingiva compared with non-inflamed gingiva. To elucidate the roles of miR-200b in the inflamed gingiva, we have analyzed the effects of miR-200b on the expression of IL-6 in human gingival fibroblasts (HGF).Materials and methodsTotal RNA and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 51 publications
3
18
0
2
Order By: Relevance
“…Given its inflammatory potential, the NF-κB signaling pathway is tightly regulated by proteins including inhibitor of NF-κB alpha (IκBα), which prevents NF-κB nuclear translocation and transcriptional activation until immunoproteasome-mediated IκBα degradation occurs (Suryavanshi & Kulkarni, 2017;Zhu, Han, Yuan, Xue, & Pang, 2018). The IKK complex is composed of three subunits each encoded by a separate gene, including IKKα, IKKβ, and IKKγ (Ben et al, 2019;Matsui et al, 2018); in which, IKKβ is critical for the production of inflammatory cytokines and associated with the activation of cancers, including breast cancer, pancreatic cancer, melanoma, and acute myeloid leukemia (Greten et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Given its inflammatory potential, the NF-κB signaling pathway is tightly regulated by proteins including inhibitor of NF-κB alpha (IκBα), which prevents NF-κB nuclear translocation and transcriptional activation until immunoproteasome-mediated IκBα degradation occurs (Suryavanshi & Kulkarni, 2017;Zhu, Han, Yuan, Xue, & Pang, 2018). The IKK complex is composed of three subunits each encoded by a separate gene, including IKKα, IKKβ, and IKKγ (Ben et al, 2019;Matsui et al, 2018); in which, IKKβ is critical for the production of inflammatory cytokines and associated with the activation of cancers, including breast cancer, pancreatic cancer, melanoma, and acute myeloid leukemia (Greten et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The miR-200 family, including miR-429, has been studied for its biological function and aberrant expression in various diseases, particularly in tumors (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)35,36). Although several studies demonstrate that miR-429 exerted anti-inflammatory activities in some diseases (35,36), further investigation is necessary to fully understand its biological Figure 4.…”
Section: Discussionmentioning
confidence: 99%
“…Among miRNAs, miR-429, a member of miR-200 family, is studied as an epithelial mesenchymal transition-associated miRNA and is often found to be dysregulated in various types of malignant tumors including oral squamous cell carcinoma (16)(17)(18)(19). Previous studies have reported that miR-429 and its family miRNAs suppress the expression of multiple genes involved in inflammatory signaling and production of interleukins, particularly IL-8 (16)(17)(18)(20)(21)(22)(23)(24)(25)(26)(27). The evidence for the relevance and function of miR-429 in pathological and physiological events has accumulated; however, the possible association of miR-429 with oral inflammatory processes remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…ZEB1 is involved also in inflammatory processes. Suppression of ZEB1 by miR‐200b leads to a decrease in IL‐6 production in gingival fibroblasts …”
Section: Introductionmentioning
confidence: 99%
“…Suppression of ZEB1 by miR-200b leads to a decrease in IL-6 production in gingival fibroblasts. 24 Little is known about ZEB1 expression in oral diseases. TWIST1 and ZEB1 are upregulated in oral submucous fibrosis, which is a potentially malignant condition.…”
mentioning
confidence: 99%